2018
DOI: 10.1096/fj.201800113r
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐205 suppresses tumor growth, invasion, and epithelial‐mesenchymal transition by targeting SEMA4C in hepatocellular carcinoma

Abstract: Growing evidence indicates that microRNAs are involved in tumorigenesis and progression of hepatocellular carcinoma (HCC). However, the functional mechanisms of miR-205 in HCC remain largely unknown. Here, we demonstrate that miR-205 expression was significantly down-regulated in HCC tissues and cell lines and was correlated with metastatic pathologic features and shorter disease-free and overall survival. Overexpression of miR-205 dramatically inhibited HCC cell proliferation, apoptosis, migration, invasion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…miR-205 can inhibit the proliferation and migration of tumor cells by targeting RUNX2 in pancreatic cancer (18). Lu et al (19) confirmed that the expression of miR-205 in HCC cells decreased, which could inhibit the migration and invasion of HCC cells. miR-205 may become a therapeutic target for HCC.…”
Section: Discussionmentioning
confidence: 97%
“…miR-205 can inhibit the proliferation and migration of tumor cells by targeting RUNX2 in pancreatic cancer (18). Lu et al (19) confirmed that the expression of miR-205 in HCC cells decreased, which could inhibit the migration and invasion of HCC cells. miR-205 may become a therapeutic target for HCC.…”
Section: Discussionmentioning
confidence: 97%
“…192 Moreover, miR-205 inhibited tumor growth, invasion, and EMT via targeting semaphorin 4C in hepatocellular carcinoma. 193 Furthermore, the upregulation of miR-183-5p induced apoptosis and inhibited EMT, proliferation, invasion, and migration by the downregulation of ezrin in human endometrial cancer cells. 194 Collectively, EMT is inhibited by many miRNAs, including miR-145, miR-497, miR-145-5p, miR-138, miR-200a, miR-200b, miR-655, miR-30-5p, and miR-32.…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…For example, miRNA‐497/Wnt3a/c‐Jun regulated growth and EMT, and miR‐497 served as a tumor suppressor in glioma cells . Moreover, miR‐205 inhibited tumor growth, invasion, and EMT via targeting semaphorin 4C in hepatocellular carcinoma . Furthermore, the upregulation of miR‐183‐5p induced apoptosis and inhibited EMT, proliferation, invasion, and migration by the downregulation of ezrin in human endometrial cancer cells .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…miR-2392 suppresses metastasis and EMT by targeting MAML3 and WHSC1 in gastric cancer (6). miR-205 suppresses tumor growth, invasion, and EMT by targeting SEMA4C in hepatocellular carcinoma (7). However, the implication of miRNAs in colon cancer remains to be clarified.…”
mentioning
confidence: 99%